A Flexible Self‐Powered UV Photodetector and Optical UV Filter Based on β‐Bi2O3/SnO2 Quantum Dots Schottky Heterojunction. Issue 15 (11th July 2021) - Praveen, Shanigaram; Veeralingam, Sushmitha; Badhulika, Sushmee
Abstract: Recently reported ultraviolet (UV) detectors majorly focus on exploration of photodetection properties like photon absorption and electron‐hole pair generation to improve the photoresponsivity. However, UV sensors also have a potential advantage of monitoring the excessive UV exposure on skin. In this work, bismuth oxide/SnO2 quantum dots (QDs) vertical‐junction‐based self‐powered UV photodetector and optical UV filter are demonstrated. β‐Bi2 O3 nanofibers are synthesized via electrospinning technique and SnO2 QDs are synthesized using a facile, single step hydrothermal process. Detailed morphological studies reveal the formation of 1D‐Bi2 O3 and 0D‐SnO2 . The fabricated self‐powered Bi2 O2 /SnO2 ‐based p–n heterojunction device exhibits a maximum responsivity of 62.5 µ A W −1 and specific detectivity (D*) of 4.5 × 109 Jones attributing to the high absorption coefficient of β‐Bi2 O2 nanofibers and SnO2 QDs in the UV region. Further, the 1D β‐Bi2 O3 nanofibers and 0D SnO2 QDs are coated onto disposable cloth substrate to fabricate the UV optical filter which exhibits an exceptional ultraviolet protection factor of 159 and the photodetector device demonstrates high stability and reproducibility even after 1000 bending cycles. The strategy outlined here paves the way for development of bifunctional, cost‐effective design and construction of wearable UV sensors and protective devices for advanced nano‐electronic applications. Abstract : Flexible self‐powered solar‐blind photodetector and ultraviolet (UV) filter based on β‐Bi2 O3 nanofibers/SnO2 quantum dots Schottky heterojunction is demonstrated. The UV filter is fabricated by decorating Bi2 O3 and SnO2 quantum dots on polypropylene cloth which exhibits an excellent ultraviolet protection factor of 159.